Effectiveness of emergency care practitioners working within existing emergency service models of care. Issue 4 (23rd March 2007) - Mason, Suzanne; O'Keeffe, Colin; Coleman, Patricia; Edlin, Richard; Nicholl, Jon
Abstract : Background: An emergency care practitioner (ECP) is a generic practitioner drawn mainly from paramedic and nursing backgrounds. ECPs receive formal training and extended clinical skills to equip them to work as an integral part of the healthcare team working within and across traditional boundaries of emergency and unplanned care. Currently, ECPs are working in different healthcare settings in the UK. Objectives: (1) To evaluate appropriateness, satisfaction and cost of ECPs compared with the usual service available in the same healthcare setting, (2) to increase understanding of what effect, if any, ECPs are having on delivery of health services locally and (3) to evaluate whether ECP working yields cost savings. Methods: Using a mixed-methods approach, data were collected quantitatively and qualitatively from three different types of health provider setting where ECPs are operational, in three areas of England. Data were collected by sending two questionnaires to each patient eligible to be seen by an ECP, at 3 and 28 days after presentation; telephone interviews were conducted with a sample of staff that included ECPs, other health professionals and stakeholders (eg, managers) in each of the three settings; and routine data were analysed to provide a perspective on costs. Results: After adjusting for age, sex, presenting complaint and service model, some differences in the processes of care between the ECPs and the usual providers in the three settings were observed. Overall, ECPs carried out fewer investigations, provided more treatments and were more likely to discharge patients home than the usual providers. Patients were satisfied with the care received from ECPs, and this was consistent across the three different settings. It was found that ECPs are working in different settings across traditional professional boundaries and are having an impact on reconfiguring how those services are delivered locally. Costs information (based on one site only) indicated that ECP care may be cost effective in that model of ECP working. Conclusion: Care provided by ECPs appears to reduce the need for subsequent referral to other emergency and unscheduled care services in a large proportion of cases. We found no evidence that the care provided by an ECP was less appropriate than the care by the usual providers for the same type of health problem.